The Relationship between Performance Motivation and Career Development on Nurse Job Satisfaction at the Banjarmasin City Health Center - Camelia Rizqi, Maulidha; Irawan, Angga; Basit, Mohammad; Arief Wijaksono, Muhammad (Universitas Muhammadiyah Kalimantan Timur, 2024)
Nurse job satisfaction is a nurse's assessment of performance results and the place of work. Job satisfaction can be influenced by the work environment, so performance motivation is needed to complete tasks. Apart from that, satisfactory performance results require knowledge by means of career development. The aim of this research is to determine the relationship between performance motivation and career development on job satisfaction for nurses at the Banjarmasin City Health Center. This quantitative research used a cross sectional approach which was carried out at 3 Banjarmasin City Health Centers, namely Pekauman, Pelambuan, and Sungai Jingah Community Health Centers. Activities were carried out in March-May 2024. The population in this study were all nurses who worked in 3 Banjarmasin City Health Centers totaling 22 nurses. Sampling used total sampling. The instrument uses a performance motivation, career development and job satisfaction questionnaire. The questionnaire was declared valid and reliable. In the nurse performance questionnaire, the validity value was >0.4227 with a reliability of 0.910. The validity of the career development questionnaire is >0.361 with a reliability of 0.945. In the job satisfaction questionnaire, the validity is >0.4227 with a reliability of 0.894. The results of the analysis showed that the majority of nurses' performance motivation was classified as good, namely 13 nurses (59.1%). Career development was stated to be high by 13 nurses (59.1%). A total of 11 nurses stated that their job satisfaction was in the high category and 11 nurses stated that they were in the medium category. The results of the Spearman Rank test obtained a p-value of 0.001 in the performance motivation test with nurses' job satisfaction and the analysis of career development with nurses' job satisfaction. So it is concluded that there is a relationship between performance motivation and career development and nurse job satisfaction. The direction of the positive relationship means that the higher the performance motivation and career development of nurses, the higher their job satisfaction.